2010
DOI: 10.1073/pnas.1002262107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and reversal of synaptic defects in the amygdala in a mouse model of fragile X syndrome

Abstract: Fragile X syndrome (FXS), a common inherited form of mental impairment and autism, is caused by transcriptional silencing of the fragile X mental retardation 1 (FMR1) gene. Earlier studies have identified a role for aberrant synaptic plasticity mediated by the metabotropic glutamate receptors (mGluRs) in FXS. However, many of these observations are derived primarily from studies in the hippocampus. The strong emotional symptoms of FXS, on the other hand, are likely to involve the amygdala. Unfortunately, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 41 publications
8
108
0
1
Order By: Relevance
“…Moreover, Harlow et al (2010) demonstrated impaired synaptic plasticity in the barrel cortex in Fmr1 KO mice during the critical period, a process that was shown to involve FMRP and mGlu 1/5 activity (Todd et al, 2003). Another study reported aberrant mGlu 1/5 -dependent neuronal plasticity in the amygdala of Fmr1 KO mice (Suvrathan et al, 2010). Furthermore, a specific, mGlu 1/5 -and protein synthesis-dependent form of hippocampal LTP was shown to be dysregulated in Fmr1 KO mice (Shang et al, 2009), and a recent study demonstrated that mGlu 1/5 -mediated priming of hippocampal LTP is, in contrast to wild-type, protein synthesisindependent in Fmr1 KO mice (Auerbach and Bear, 2010).…”
Section: Other Mglu 1/5 -Dependent Mechanisms In Fxsmentioning
confidence: 96%
“…Moreover, Harlow et al (2010) demonstrated impaired synaptic plasticity in the barrel cortex in Fmr1 KO mice during the critical period, a process that was shown to involve FMRP and mGlu 1/5 activity (Todd et al, 2003). Another study reported aberrant mGlu 1/5 -dependent neuronal plasticity in the amygdala of Fmr1 KO mice (Suvrathan et al, 2010). Furthermore, a specific, mGlu 1/5 -and protein synthesis-dependent form of hippocampal LTP was shown to be dysregulated in Fmr1 KO mice (Shang et al, 2009), and a recent study demonstrated that mGlu 1/5 -mediated priming of hippocampal LTP is, in contrast to wild-type, protein synthesisindependent in Fmr1 KO mice (Auerbach and Bear, 2010).…”
Section: Other Mglu 1/5 -Dependent Mechanisms In Fxsmentioning
confidence: 96%
“…For a more extensive review of Fmr1 knockout mice behavioral phenotypes see [180]. Behavior: social dominance [119]; sociability [132] Cognition: object recognition (chronic, not acute) [121]; fear conditioning [120]; associative motor learning (acute) [133]; inhibitory avoidance (chronic and acute) [129,133]; extinction memory (chronic) [129] LTP deficits in the amygdala and hippocampus (bath application) [128,134]; LTD (bath application) [135] startle response, † rotarod performance [131]; object recognition (acute) [121,134]; coordinate and categorical tasks (acute) [134]; analgesic response [121] mGlu5 NAMs used:…”
Section: Macro-orchidismmentioning
confidence: 99%
“…• MPEP [43,62,63,97,123,126,128,130,131,134] • MTEP [121] • Fenobam [124,126,133] • AFQ056 [119,125,127,132] CTEP [120,129] mGlu1 Genetic (het) Hyperexcitability: locomotor activity [118] Macro-orchidism, PPI, startle response, AGS, social interaction [118] Pharm Hyperexcitability: AGS (partially) [131] Startle response, rotarod [131] Muscarinic R (subtypes M1 and M4) Genetic (het) Plasticity and hyperexcitability: analgesic response, startle response (M4) [136] PPI, MB, light-dark transition (anxiety), AGS, macro-orchidism [136] Pharm Plasticity and hyperexcitability: AGS (M1+M4) [137,138] Cognition: passive avoidance (M4) [138] Passive avoidance (M1) [137] Group II mGlu N/A GSK3β antagonists used:…”
Section: Macro-orchidismmentioning
confidence: 99%
“…Loss of FMRP has been linked to various forms of long-term synaptic plasticity defects that depend on local protein synthesis in the postsynaptic neuron (3). In addition to disrupted metabotropic glutamate receptor signaling, which has been shown across multiple brain regions (4)(5)(6)(7), FMRP is necessary for activitydependent protein synthesis downstream of other signaling receptor pathways, including ACh, dopamine, and TrkB (8)(9)(10).…”
mentioning
confidence: 99%